Using Simulation to Support Evidence-Based Design of Safer Health Care Environments - Halamek, Louis P. (American Journal of Perinatology, 2022)
The design of health care environments and the technologies used within them have tremendous influence on the performance of the professionals who care for patients in those spaces. In turn, the performance of those professionals greatly impacts the safety of the care that is delivered to patients. Active and latent safety errors can be greatly reduced by rigorous testing of the patient care environment.While there are numerous types of testing that can be conducted, this manuscript will focus on the use of simulated clinical scenarios in realistic/real physical environments to detect and remediate weaknesses in the design of those environments with a focus on their use in perinatal centers.Key Points
Keywords: simulation; debriefing; perinatal; mothers and babies; evidence-based design; patient safety